Combining Sample Designs to Account for the Whole Necromass Carbon Stock in Brazilian Atlantic Forest. (3rd October 2021) - Maas, Greyce C. B.; Sanquetta, Carlos R.; Marques, Renato; Machado, Sebastião Do A.; Sanquetta, Mateus N. I.; Corte, Ana P. Dalla; Schmidt, Luciane N.
ABSTRACT: Necromass is crucial to understanding both carbon and nutrient cycling throughout the forest. In this study, we assessed the carbon stock and spatial distribution of necromass components in an Atlantic rainforest, southern Brazil, one hotspot of biodiversity. Necromass comprised: standing dead trees and stumps ( SWN ), large-sized woody necromass ( LWN ), medium-sized woody necromass ( MWN ), and litter ( LTR ). Specific sample designs assessed each component, while the Payandeh index indicated spatial distribution. Mean wood densities of LWN ranged from 0.24 to 0.46 g.cm −3, and mean carbon fraction ranged from 0.42 to 0.44 gC.g −1 d.m. depending on decay class. The total necromass carbon stock was 12.83 MgC.ha −1 . SWN, LWN, MWN, and LTR carbon stores were 3.15, 4.24, 1.50, and 3.53 MgC.ha −1, respectively. LWN and MWN showed a reverse J-curve skewed carbon stock distribution and clumped spatial pattern. LTR presented asymmetric distribution and a random spatial pattern. Coarse and heavy necromass is clumped near dead trees, while the wind scatters fine necromass throughout the forest. This study provides useful information to the understanding of the carbon cycle in Atlantic rainforests and may be helpful to improve the Brazilian Inventory of Anthropogenic Emissions and Removals of Greenhouse Gases and the Global Forest Resource Assessment.